Improving Carrageenan Extraction Efficiency and Stability Using KOH, NaOH, and Anti-Caking Agents - Heriyanto, Heri; Dewi Yasya, Annisa; Rahma Putri, Azzahra; Suhendi, Endang; Kanani, Nufus; Pujiastuti, Hendrini (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2025)
This study investigates the impact of varying concentrations of potassium hydroxide (KOH) and sodium hydroxide (NaOH), along with anti-caking agents, on the quality of carrageenan extracted from Eucheuma cottonii seaweed. FTIR analysis revealed that KOH-extracted carrageenan retained key functional groups, including sulfate esters and glycosidic bonds, essential for its classification as kappa-carrageenan. KOH also proved more effective than NaOH in reducing moisture content, preserving structural integrity, and meeting the Indonesian National Standards (SNI) for carrageenan quality. The addition of anti-caking agents further optimized product stability, particularly in moisture control. The result shows that KOH was more effective than NaOH in improving carrageenan yield, with a yield of 46% achieved using 12% KOH and 4 g TCP. Anti-caking agents like tricalcium phosphate improved the products moisture control and stability. Future research should focus on refining extraction methods to enhance both product quality and yield.